PERENCANAAN UNIVERSITY GREEN CORRIDOR Jalur Hijau Penghubung Ruang Terbuka Antar Universitas di Wilayah Kecamatan Depok Kabupaten Sleman DIY - Bondan Prihastomo (Jurnal Tekno Global, 2016)
It is undeniable that the Earth's temperature over time is increasing. This we know as global warming. This is evident since 1880 where the Earth's average temperature rise of 0.8 ° C. A drastic improvement occurred in recent decades. According to NASA's Goddard Institute for Space Studies, areas that have been affected most from global warming is an urban area, so experts are racing to figure out how to overcome, suppress and improve the natural conditions for the life of mankind for a better life. One way that can be done for the problem of global warming is to create green open spaces in urban areas. Green Line system is the most effective solution to provide shade areas as quality improved comfort for pedestrians and other road users. Sleman is one part of the city of Yogyakarta, which is becoming increasingly congested by vehicles and settlements. Therefore there is need for improvement of the quality of the green line so that the quality of urban space to be better. In this paper will discuss the concept of the green line which is interconnected with a network of green cities with more emphasis on pedestrian path along the road that connects several major Universities in Sleman.Keywords: Green Line Systems, corridors and pedestrian